Improving smallholder farmers' gross margins and labor-use efficiency across a range of cropping systems in the Eastern Gangetic Plains. (February 2021) - Gathala, Mahesh K.; Laing, Alison M.; Tiwari, Thakur P.; Timsina, Jagadish; Rola-Rubzen, Fay; Islam, Saiful; Maharjan, Sofina; Brown, Peter R.; Das, Kalyan K.; Pradhan, Kausik; Chowdhury, Apurba K.; Kumar, Ranvir; et al.
Highlights: Conservation agriculture-based sustainable intensification participatory research. Reduced both labor use and production costs by 40%. Increased gross margins by up to 25%. Reduced drudgery for women and youth who do the majority of menial, laborious tasks. Results applicable for a wide range of smallholder farming communities. Abstract: The Eastern Gangetic Plains of South Asia is a region of high rural poverty and low agronomic productivity, with crops grown using traditional management practices which are labor-intensive and uneconomical. Poor agronomic productivity is largely caused by unintentional, inefficient management practices which are exacerbated by labor shortages caused by increased migration away from rural areas as households require additional income from remittances. These labor shortages increase the cost of hiring labor, further contributing to low gross margins from cropping systems. The climates, soils and available water across the region indicate that, with improved management practices, this region has the potential to produce high yields for low production costs and labor requirements, ensuring high gross margins for smallholder farmers. We conducted on-farm participatory trials to compare the performance of traditional and improved conservation agriculture-based sustainable intensification management practices to understand which used less labor, had lower production costs and returned higher gross margins to smallholder farmers. Our study showed that compared to traditional management practices, conservation agriculture-based sustainable intensification practices reduced both labor use and total cropping system production costs by around 40% and increased gross margins by up to 25%. Trials were conducted on over 400 farms and thus our results are both statistically rigorous and representative of a range of common crop production management across the Eastern Gangetic Plains. These results show there is potential to increase livelihoods and reduce the impact of labor shortages for smallholder farmers living in diverse climatic, edaphic and social circumstances across the region. They have broader applications in labor-constrained smallholder cropping systems throughout South Asia and worldwide.